Redescription of Antarctophthirus lobodontis (Anoplura: Echinophthiriidae) from the crabeater seal and identification key for Antarctic lice - Leonardi, María Soledad (2016)
The Anoplura (Phthiraptera) is composed of lice parasitizing mainly terrestrial mammals, but a few members have been able to adapt to the marine environment. The latter are included in the family Echinophthiriidae, a particular group infecting pinnipeds worldwide. They also are of the few insects that managed to survive in the ocean. The study of Antarctic echinophthiriids flourished in the 1960s, but in the last 50 years, no advance has been made. Revision of Antarctic echinophthiriids is part of ongoing research on the systematics, phylogeny and ecology of these lice. During the summer season of 2014, we had the opportunity to collect lice from crabeater seals captured at Cierva Cove in the northern sector of the Danco Coast, Antarctic Peninsula. Since its original description was incomplete and the holotypes were lost, here we redescribe Antarctophthirus lobodontis based on these specimens. The present material can be distinguished from other Antarctic Antarctophthirus species by the presence of four marginal long hairs and in the basis of the head a line of eight spines and three hairs above the last row of four spines. Also in the present work, we provide a key to the identification of the Antarctic species of Echinophthiriidae based on morphological characteristics.